Local Level Institutional Self-Assessment System: Technological Innovation in Public Sector - Kandel, Resham (Prashasan: The Nepalese Journal of Public Administration, 2021)
After restructuring the governance system from unitary to federal with substantial power and resources to local level, web based Local Government Institutional Capacity Self-Assessment (LISA) system has been introduced as an innovative tool to track the performance of local governments in Nepal. The LISA intends to improve local governance which can be considered as a public sector innovation following the global trend of ICT development and e-governance. The incentive mechanism and institutional readiness are the crucial components to internalize the new system in any organization. The study illustrates that these components are poorly addressed in LISA which challenges the sustainability of the system. Moreover, the analysis shows that the issues of legal ground of the system, rewarding mechanism, IT infrastructures and IT friendly human resources at local level, quality assurance and data security, etc. are not adequately addressed to fully implement the system in future. Furthermore, capacity development and technical backstopping to the local governments are essential to make the system successful in tracking the performance of local levels. In this regard, this article presents a case of web-based institutional performance assessment system implemented at the local level governance.